Role of p110a subunit of PI3-kinase in skeletal muscle mitochondrial homeostasis and metabolism - Mengyao Ella Li; Hans P. M. M. Lauritzen; Brian T. O’Neill; Chih-Hao Wang; Weikang Cai; Bruna B. Brandao; Masaji Sakaguchi; Rongya Tao; Michael F. Hirshman; Samir Softic; C. Ronald Kahn (Nature Communications, 2019)
Diabetes is associated with decreased PI3K activation in skeletal muscle. Here, the authors show that p110a is the predominant PI3K subunit in muscle, and show that its ablation in muscle, but not ablation of p110beta, leads to insulin resistance, increased proteosomal and autophagic activity, and altered mitochondria homeostasis in mice.